Pathways of apoptosis in muscle 1 - Alway, Stephen E. (Henry Stewart Talks, 2018)
Introduction to apoptosis in skeletal muscle, Nuclear apoptosis, Apoptotic signaling during muscle wasting, Denervation-induced muscle wasting, Unloading/disuse -associated muscle wasting, Id2 signaling in apoptosis; aging and muscle disuse, Unloading followed by reloading and apoptosis, Apoptosis signaling pathways in aging-induced sarcopenia, Cross-talk between extrinsic and mitochondrial signaling pathways